Development of teaching and learning prototype for learning disabilities students using interactive multimedia approach / Hazeian Omar - Omar, Hazeian (Faculty of Information Technology and Quantitative Sciences, 2005)
Multimedia presentation is widely accepted as a successful learning aid that proved to enhance the interest and the skill of the targeted audience. With the interactive features found in the presentation, the multimedia learning approach has widely been accepted all around the world. Teaching and Learning prototype for Learning Disabilities Student also are now available in the multimedia presentation. Teaching and Learning prototype for Learning Disabilities Student is develop specifically for learning disabilities students from age 6 years to 14 years old. The content of the Teaching and Learning prototype for Learning Disabilities Student are including Teaching Syllabus and Exercise. The Teaching syllabus is including Alphabet Number, My First Numbers, Rainbows Color, Shape of Objects and social and Self-Help. Beside that the Exercise is including Label the Picture, Objective Questions and Complete the Words. In developing the Teaching and Learning prototype for Learning Disabilities Student, methodology are consists of Project Conceptualization , Planning , organizing and research , Developing digital media content, Multimedia authoring, packaging and delivery and lastly presentation is used. The data is collected through observation on special educational school and interviews with the teacher. The Teaching and Learning prototype for Learning Disabilities Student is develop in an interactive multimedia approach that can enhance the learning disabilities students intention and encourage them to learn and feel enjoyable on their studies.